The environmental performance of enhanced metal recovery from dry municipal solid waste incineration bottom ash. (1st January 2021) - Mehr, Jonas; Haupt, Melanie; Skutan, Stefan; Morf, Leo; Raka Adrianto, Lugas; Weibel, Gisela; Hellweg, Stefanie
Highlights: We assess environmental benefits of enhanced metal recovery from MSWI bottom ash. Primary metal substitution dominates environmental savings in the short run. The quality of the recovered metal fractions drives its substitution potential. The recovery of heavy non-ferrous metals shows great ecological potential. Enhanced metal recovery contributes substantially to an impact reduction of MSWI. Abstract: This study assesses the environmental performance of the municipal solid waste (MSW) incineration bottom ash (IBA) treatment plant in Hinwil, Switzerland, a large-scale industrial plant, which also serves as a full-scale laboratory for new technologies and aims at an optimal recovery of metals in terms of quantity and quality. Based on new mass-flow data, we perform a life cycle assessment that includes the recovery of iron, stainless steel, aluminium, copper, lead, silver and gold. Fraction-specific modelling allows for investigating the effect of the metal fraction quality on the subsequent secondary metal production as well as examining further metal recycling potentials in the residual IBA. In addition, the implications on the landfill emissions of IBA residues to water were quantified. The impact assessment considered climate change, eco- and human toxicity and abiotic resource depletion as indicators. Results indicate large environmental savings for every impact category, due to primary metal substitution and reduction of long-term emissions from landfills. Metal product substitution contributes between 75% and >99% to these savings in a base scenario (1′000-year time horizon), depending on the impact category. Reductions in landfill emissions become important only when a much longer time horizon was adopted. The metal-based analysis further illustrates that recovering heavy non-ferrous metals – especially copper and gold – leads to large environmental benefits. Compared to the total net savings of energy recovery (215 kg CO2 -eq per tonne of treated waste, average Swiss plant), enhanced metal recovery may save up to 140 kg CO2 -eq per tonne of treated waste.